Indonesian-English Fable Characters’ Representation and Authors’ Worldview - Terra Patriana (Universitas Pendidikan Indonesia (UPI), 2013)
The present research investigates how animals as characters are represented in Indonesian and English fables and the authors’ worldview through the fable they rewrite. It is descriptive with the element of quantitative in the form of percentages. The main theoretical framework of the research is transitivity and theme-rheme as proposed by Halliday and his followers. “Si Kancil dan Siput” and “The Tortoise and The Hare” which were downloaded October 2012 from childhoodreading.com and www.ceritaanak.org have been used as the source of the data. The research finds that Indonesian author sees animals as the sayer (verbal process), and usually do things without too much considerations, while English author sees animals as the being (behavioural process), in which besides doing actions, animals also sense it. Furthermore, English fable considers participants of the events as the important aspect in the story, and as the departure of events more than Indonesian fable does. Keywords: SFL, Transitivity, Theme-Rheme, Thematic Progression, Fables, Worldview